Morphological features of Dieulafoy’s lesion. Clinical case. - Pyatikop, G.; Moskalenko, R.; Kravets, O.; Bratushka, V.; Tkach, G. (Морфологія / Morphologia / Morfologìâ, 2012)
The paper highlights a rare Dieulafoy’s lesion. At autopsy study found a slight defect of the gastric mucosa in the upper part of the greater curvature, in the center of which there was a thrombotic vessel. Histological examination revealed the plot of erosive mucous membrane, occurrence of fibrinoid necrosis, the artery with uneven walls and thickness defect, dysplastic vessels under the muscle plate of mucosa, lymphocytic infiltration in the surrounding areas of the mucosa.